The framing effect of tax–transfer systems - He Tai-Sen (2020)
The present study investigates the framing effect of tax–transfer systems on work effort decisions. We devised two theoretically equivalent treatments—the redistributive tax treatment and the redistributive transfer treatment—and studied subjects’ work effort choices in a novel public goods experiment. We found that subjects chose higher effort levels when redistribution took place via transfers than via taxes. Interestingly, the treatment effect was more pronounced among those with lower cognitive abilities and those who judged the tax–transfer system to be unfair. The results have the potential to offer insight on the debate about the extent to which taxes or transfers should be actively used for redistribution.